Vulvovaginal symptoms prevalence in postmenopausal women and relationship to other menopausal symptoms and pelvic floor disorders. Issue 4 (April 2016) - Erekson, Elisabeth A.; Li, Fang-Yong; Martin, Deanna K.; Fried, Terri R.
Abstract : Supplemental Digital Content is available in the text Abstract: Objective: The primary objective of this study was to use the Vulvovaginal Symptom Questionnaire (VSQ) to estimate the prevalence and examine the emotional, lifestyle, and sexual impact of vulvovaginal symptoms in postmenopausal women. Methods: We administered the VSQ, a previous validated instrument to 358 postmenopausal women recruited from primary care physician offices and local senior centers. The first seven questions of the VSQ comprise the symptom subscale (itching, burning, hurting, irritation, dryness, discharge, and odor). Women who answered "Yes" to any of the first seven symptom questions were considered to have vulvovaginal symptoms. Results: Two hundred seventy-nine women were recruited from primary care offices and 79 women were recruited from senior centers. One hundred eighty-three postmenopausal women (51.1%; 95% CI 45.9%, 56.3%) reported at least one vulvovaginal symptom. The most common symptom was being dry 35.8% (n/N = 128/358). Ten percent of women (n/N = 38/358) reported five or more symptoms and 6% of women reported all seven symptoms in the last week. For women reporting one or more vulvovaginal symptoms, 40.4% (n/N = 74/183) reported emotional impact (Yes to ≥1 out of 4 emotional impact subscale items) and 32.8% (n/N = 60/183) reported lifestyle impact (Yes to ≥1 out of 5 lifestyle impact subscale items) from these symptoms. For sexually active women reporting vulvovaginal symptoms, 75.3% (n/N = 67/89) reported sexual impact (Yes to ≥1 out of 4 sexual impact subscale items). Vulvovaginal symptoms were associated with increased co-occurrence of specific pelvic floor disorders, including pelvic organ prolapse ( P  = 0.001), anal incontinence to solid stool ( P  = 0.001), urinary frequency ( P  = 0.02), urgency urinary incontinence ( P  = 0.001), and dysuria ( P  < 0.001). Conclusions: Vulvovaginal symptoms are common and present in over 50% of postmenopausal women. Sizeable proportions of women with vulvovaginal symptoms report emotional, lifestyle, and sexual impact from these symptoms.